2020
DOI: 10.1080/10942912.2020.1754234
|View full text |Cite
|
Sign up to set email alerts
|

Study of the protein, antioxidant activity, and starch duringin vitrosimulated digestion of green wheat and wheat cooked flours

Abstract: View related articlesView Crossmark data Citing articles: 4 View citing articlesStudy of the protein, antioxidant activity, and starch during in vitro simulated digestion of green wheat and wheat cooked flours

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…It was reported that the protein content of green wheat is 14.9%, while this content is 11.9% in mature wheat (Zhang & Zhang, 2019). In addition, the mineral composition of green wheat shows high amounts of potassium, calcium, and magnesium (Zhang, Yang, et al, 2020). It is worth noting that the higher content of dietary fiber in green wheat is beneficial to human intestinal digestion and detoxification.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the protein content of green wheat is 14.9%, while this content is 11.9% in mature wheat (Zhang & Zhang, 2019). In addition, the mineral composition of green wheat shows high amounts of potassium, calcium, and magnesium (Zhang, Yang, et al, 2020). It is worth noting that the higher content of dietary fiber in green wheat is beneficial to human intestinal digestion and detoxification.…”
Section: Introductionmentioning
confidence: 99%
“…However, green wheat has low starch content and is not conducive to the formation of gluten protein. It is often mixed with flour to make food, such as green wheat cakes and green wheat noodles (Zhang, Xu, et al, 2021; Zhang, Yang, et al, 2020; Zhang, Zhang, et al, 2020; Zhang, Zhang, et al, 2021; Zhang, Zhao, et al, 2021). However, there are few studies on the effect of the amount of green wheat flour on the quality of steamed bread.…”
Section: Introductionmentioning
confidence: 99%
“…Green wheat has the taste of fresh wheat flavor, and it is also rich in protein (14.90%), dietary fiber (12.88%), ferulic acid (1.444%), and a variety of nutrients higher than those of mature wheat (Zhang & Zhang, 2019). As a healthy food, green wheat grains can help the body digest and stabilize blood sugar (Zhang, et al, 2020a, 2020b). It has a good development prospect because of the economic value and market prospect that are widely accepted by the public.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, green wheat can be freeze‐dried and made into flour then added to other foods. Up to now, the studies of green wheat have mainly focused on starch modification, digestive properties, and applications (Zhang, et al, 2020a, 2012b, 2021, 2020d). However, only few studies have been investigated on the volatile compositions of green wheat.…”
Section: Introductionmentioning
confidence: 99%